Hubungan perilaku personal hygiene dengan keputihan di PMB Kabupaten Tangerang - Haeriyah, Siti; Novianti, Rosa (Jurnal Nusantara Mandani, 2022)
Background: According to the World Health Organization (WHO) including regenerative medical conditions, pregnant women experience vaginal discharge by 30.6% caused by the organism Candida albicans. Judging from the Indonesian Health Profile, one of the cases found in pregnant women was vaginal discharge as much as 16%, namely Candida 53%, Trichomonas 3.1% and delegated Microorganisms 40.1%. Subject and method : This study uses a cross sectional method of sampling using a total sampling technique, that is, all members of the population are used as samples. This research was conducted in October-November 2021. The target population in this study were all pregnant women who were taken in October. The sampling technique used in this study uses a total sampling technique. The sample in this study were all pregnant women in PMB Tangerang City in 2021 as many as 53 pregnant women. The measuring instrument of this research used a Personal Hygiene questionnaire sheet. The research data was processed using the Chi Square test. Results: Of the 53 respondents, 37 respondents (69.8%) had poor personal hygiene behavior. good personal hygiene behavior 16 respondents (30.2%) p value 0.003. OR = 9,028 (2.157 – 37.789). Conclusion : so there is a relationship between personal hygiene behavior with vaginal discharge in pregnant women. This means that mothers with poor personal hygiene have a 9,028 times greater chance of experiencing vaginal discharge compared to mothers with good personal hygiene. Keywords : Personal hygiene behavior, vaginal discharge